2008
DOI: 10.1177/1525822x07307463
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Qualitative and Quantitative Findings in Mixed Research Synthesis Studies

Abstract: The synthesis of qualitative and quantitative research findings is increasingly promoted, but many of the conceptual and methodological issues it raises have yet to be fully understood and resolved. In this article, we describe how we handled issues encountered in efforts to synthesize the findings in forty-two reports of studies of antiretroviral adherence in HIV-positive women in the course of an ongoing study to develop methods to synthesize qualitative and quantitative research findings in common domains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 29 publications
1
85
0
1
Order By: Relevance
“…Forty-one articles focused on aspects of individual resilience and eight focused on community resilience. The review utilizes an integrated design to examine quantitative, qualitative, and mixed-methods studies; this integrated design was chosen because of the potential for findings from across study designs to collectively advance knowledge about political violence and resilience (Voils, Sandelowski, Barroso, & Hasselblad, 2008). For more information about the types of methods used across studies (e.g., surveys, narrative research, ethnography/case study; mixed methods, longitudinal), see Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Forty-one articles focused on aspects of individual resilience and eight focused on community resilience. The review utilizes an integrated design to examine quantitative, qualitative, and mixed-methods studies; this integrated design was chosen because of the potential for findings from across study designs to collectively advance knowledge about political violence and resilience (Voils, Sandelowski, Barroso, & Hasselblad, 2008). For more information about the types of methods used across studies (e.g., surveys, narrative research, ethnography/case study; mixed methods, longitudinal), see Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…To accommodate the diversity of factors explored, our synthesis began by grouping findings that were topically similar and focused on producing a configuration of findings. This data-inspired synthesis did not require repetition of a factor to be included, and findings were viewed as complementing but not confirming each other (such as in meta-analyses; Voils et al 2008). Through the synthesis process it became evident that the bioecological theory for human development (Bronfenbrenner 2005) was a valuable approach to configure the findings.…”
Section: Methodsmentioning
confidence: 99%
“…The authors defined factors related to obesity and overweight to include broadly: (1) studies that addressed associated factors, covariates, and other statistical descriptions (e.g., prevalence of factor by weight status, bivariate analyses) that have been related to obesity, overweight, and/or increases in BMI or adiposity in Black girls, and (2) studies that reported individuals’ understanding and/or experience of factors related to obesity, overweight, and weight gain among Black girls. As qualitative reports using interviews and thematic analysis approaches often produce findings similar in interpretive depth to the descriptive findings in quantitative reports, the authors definition appropriately promoted the inclusion of both quantitative and qualitative investigations (Voils et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…We conducted a qualitative meta-synthesis [2531] of the five projects that comprise the PHD program – Round 2. This involved interpretation and synthesis of documents and data we collected from each of the PHD projects and examining these data to identify patterns and summarize key findings [25].…”
Section: Methodsmentioning
confidence: 99%